The influence of Tai Chi exercise on the subjective well-being in the aged: the mediating role of physical fitness and cognitive function - Heng Wang; Yangyang Liu; Zhengguo Pei; Jiafeng Liang; Xiaosheng Ding (BMC Geriatrics, 2023)
Abstract This study investigated the effects of Tai Chi exercise on subjective well-being in the aged. The participants were randomly assigned to an experimental group or a control group. The experimental group received 12-week Tai Chi exercise while the control group maintain their original living habits. The participants’ subjective well-being, physical fitness, self-control, and executive function were measured at baseline and after 12 weeks of Tai Chi exercise. Results: (1) Tai Chi exercise can positively affect the subjective well-being of the aged (F(1,78) = 37.699, p < 0.001); (2) Tai Chi exercise could affect the subjective well-being in the aged through the independent intermediary of physical fitness (95% CI=[0.115, 0.485]) and self-control (95% CI=[0.109, 0.433]); (3) Tai Chi exercise could indirectly affect the subjective well-being in the aged through the chain mediation of executive function and self-control (95% CI=[0.009, 0.104]). This study provides valuable insights into the potential benefits of Tai Chi exercise for subjective well-being in the aged.